Assessment of human impacts on select reefs of Batangas and Northern Palawan - Verdadero, Francis Xavier D. (Animo Repository, 2017)
The present study aimed to describe the extent of human impacts in 32 stations in Batangas and Palawan. Each station is a reef with an area of 400m2. Using the Reef Check protocol, and the photo-transect method, the present study investigated the densities of indicators species, benthic and coral generic composition, as well size structure of massive Porites spp. of Batangas and Palawan. Results reveal that the reefs in both provinces are suffering more from anthropogenic disturbances than natural ones. For example, fish and invertebrate surveys strongly indicate that both provinces are overfished, even if more of the indicator species were encountered in Palawan. Furthermore, low levels of sedimentation appear to be a chronic source of disturbance for both provinces, but more so in Batangas. Stations that were found to be impacted more by anthropogenic disturbances than natural ones were devoid of high value fish and invertebrate species, have lower coral cover and generic diversity, as well smaller and fewer massive Porites colonies. The present study also proposes an assessment tool that could potentially distinguish reefs that are affected more by human activities from reefs which are predominantly impacted by natural disturbances.